Hearts on the fly - Shiloh, Toni (Bethany House, a division of Baker Publishing Group, 2026)
"Jabari Hall has spent his life on the ice until an injury leaves him benched. When his teammates set him up on a blind date, he never expected to be sitting across from Val Elliott, his ex's sister. With Val's loyalty on the line and Jabari searching for a new purpose, can they make it to the goal together, or will their hearts wind up in the penalty box?"-- Provided by publisher.